The Social Face of Stigma: A Meta-Analysis of Gender, Support, and Living Environment in HIV/AIDS Perception - Utami, Indri Nur; Dewi, Rachael Saraswaty; Amalia, Rizky Nur Aprilianti; Murti, Bhisma; Veibiani, Nindita Arum (Indonesian Journal of Medicine, 2025)
Background: The stigma of society towards ODHA itself is influenced by various factors, where there are three factors that can be used as a benchmark, namely gender, place of residence, and social support. This study aims to estimate the magnitude of the influence of gender, social support and housing on the perception of stigma in people with HIV/AIDS, based on the results of a number of previous primary studies. Subject and Method: This study is a meta-analysis and systematic review study, with PICO, Population: ODHA patients (People with HIV/AIDS), Intervention: Women, low social support and village dwelling, Comparison: men, high social support and urban dwelling, Ooucome: HIV/AIDS stigma. Primary study searches used electronic databases: PUBMED, BMC, Scopus and Scient Direct published from 2012 to 2022. The keywords used are "people living with HIV" AND "gender" AND "social support" AND "residence" AND "perceived stigma HIV, cross-sectional"". There are 9 English fulltext arithmetic with effect size using adjusted odds ratio from 2012 to 2022. Articles selected with PRISMA Flow and analyzed using RevMan 5.3. Result: This meta-analysis was conducted on 9 primary studies from India and Ethiopia with a sample = 14,191 HIV/AIDS patients. This study showed that the risk of stigma perception increased with female sex (aOR=1.35, CI 95%=0.75 to 2.46; p=0.320; I²=91%) and rural housing (aOR=1.49; CI 95%=0.89 to 2.47; p=0.130), but it is not statistically significant. The risk of stigma perception decreased with high social support (aOR=0.53; CI 95%=0.32 to 0.90; p=0.020), and the results are statistically significant. Conclusion: The risk of stigma perception increases with female gender, rural housing and high social support.